LOCUS EDUCATIONIS SEBAGAI PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH MENUJU PESERTA DIDIK YANG BERBUDI - I Nyoman Sueca (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Schools can be a vehicle for character education are reliable and effective for the formation of depressed individuals. Schools can take advantage of locos educationis in educational institutions as educational praxis character. Since the first school to have two main objectives in their educational work, the human form of intelligent and virtuous. The resignation of character education, we shall ask back on yourself and on others related to relevance pendidian characters in school. If it is still relevant, how do we now want to revive, and through moments of education (locus educationis) where we can give the character education in self-learners. The destruction of moral values in a society marked by the outbreak of such violence; rape of a girl under age, murder, drugs and others, this phenomenon requires a new birth of character education in schools. Moments in a school environment that can be used as a means or opportunity to develop character education, has involved a relational network between the staff of the school with parents and the community.